Ciclo de vida y estrategias de crecimiento en la distribuidora Force Bitel, provincia de Pacasmayo, año 2018 - Ramos Leyva, Ruth Elizabeth (2019)
This research work has been carried out in Force Bitel Distributor located in the Province of Pacasmayo, Department of Freedom, in Peru. Its main objective was to determine the relationship between the Life Cycle and the Growth Strategies in the Force Bitel Distributor, in the Pacasmayo province, 2018. The respective research problem formulated was What relationship exists between the Life Cycle and Growth strategies in the Distributor Force Bitel, province of Pacasmayo, year 2018? The research was non-experimental, transectional or cross-sectional design of a correlational type; the population was conformed by the 10 workers and 410 clients of the company under study; the respective sample being the 10 workers and 78 clients, and to whom the survey technique was applied; according to the results obtained, it has been allowed to qualify the variables under study, then the analysis and discussion have been carried out, demonstrating the validity of the hypothesis that states: “There is a positive relationship between the Life Cycle and the Strategies of growth in the Force Bitel Distributor, Pacasmayo province, year 2018 ”. Finally, the main conclusion was that the life cycle has a positive relationship with the growth strategies, since identifying and knowing what life cycle the company is in has allowed it to develop the most appropriate growth strategies that allow it to continue in the current market and win more customers, hence market share.